Transformation of selected relief landforms of the Łódź Voivodeship in the last century - Twardy, Juliusz (Acta Geographica Lodziensia, 2019)
The paper presents changes in the relief of the Łódź Voivodeship over the past 100 years. In view of a shortage of data, only a few cases of changes to aeolian landforms and to selected forms appearing on the slopes of gullies and other young erosional cuts were described. The transformation of aeolian relief in the last 100 years was associated with the formation of small, initial aeolian hillocks and with the transformation by wind of older late-glacial dunes. The changes to gullies involved rapid transformation of their slope profiles under the influence of soil cultivation and comprised from 2.18 to 51.4% of the gullies’ slopes. As in the case of the dunes, the transformation of the relief both of former Neoholocene gullies, and of young, small, but permanent erosional forms originated on the slopes took place. Relief analysis of aeolian landforms and features occurring on the slopes was preceded by consideration of the vulnerability of the Łódź Voivodeship area to aeolian activity and slope processes.